Scientific and Theoretical Principles of Forming Social Activity of Students - Elvira Shikhbadinova; Elvira Zaredinova (Pedagogical Discourse, 2012)
The article is dedicated to the problem of forming social activity of students. The analysis of such notions as „Activity”, „Social Activity”, „Social Activity Of Students” is done. To learn the social activity of students. The essence of social activity is revealed and competent pattern of social activity of students is elaborated.